ACCOUNTING IS A MATTER OF TASTE. - Singer, Frank A. (The Accounting Review, 1962)
Abstract "There is no accounting for tastes," an eminent playwright assures, and all teachers have met people with no taste for accounting. Aside from the question of whether cost or market valuation shall be applied at all, it may be decided, according to someone's fancy, whether the rule shall be applied to the totals of the alternative values or to individual items or classes. The difference in result may be marked indeed. There is an uncertain distinction to be drawn which could be removed only by eliminating an alternative and that a choice may always be exercised when a situation qualifies for the pooling treatment. The clash of accounting tastes the matter of minority interest in intercompany profits suggests itself. The issue here concerns assets sold by a subsidiary, not wholly owned, which are retained by the parent at the time of preparation of consolidated reports. Taking inventory as an example, the choice lies between showing the part purchased from the subsidiary at the cost of its acquisition by the subsidiary or at this cost plus a percentage of the profit on these sales equal to the percent of minority ownership. The effect on consolidated book value of inventory would be relatively small, though the effect on minority interest might be substantial.